2020
DOI: 10.1098/rspb.2020.1919
|View full text |Cite
|
Sign up to set email alerts
|

The ammonite septum is not an adaptation to deep water: re-evaluating a centuries-old idea

Abstract: The shells of ammonoid cephalopods are among the most recognizable fossils, whose fractally folded, internal walls (septa) have inspired many hypotheses on their adaptive value. The enduring explanation for their iterative evolution is that they strengthen the shell against pressure at increasing water depths. The fossil record does not definitively support this idea and much of the theoretical mechanical work behind it has suffered from inaccurate testing geometries and conflicting results. By using a differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 42 publications
1
29
0
Order By: Relevance
“…R. Soc. B [1] refutes the idea that septal complexity in ammonoids is an adaptation to strengthen the shell against hydrostatic pressure. Although there is some evidence suggesting that septal complexity is involved in a metabolic rather than a biomechanical function [2], the author adequately indicates that there are still reminiscences of the strengthening hypothesis in some well-known textbooks.…”
supporting
confidence: 54%
“…R. Soc. B [1] refutes the idea that septal complexity in ammonoids is an adaptation to strengthen the shell against hydrostatic pressure. Although there is some evidence suggesting that septal complexity is involved in a metabolic rather than a biomechanical function [2], the author adequately indicates that there are still reminiscences of the strengthening hypothesis in some well-known textbooks.…”
supporting
confidence: 54%
“…Recent approaches have used sophisticated modeling techniques to explore shell stress. Simulations by Lemanis 44 demonstrate that higher-order folds, characteristic of ammonitic septa, do not reduce the tensile stress of the shell, however, increased point load resistance is suggested 45 . Johnson et al 46 investigated shell strength by performing physical compression experiments on 3D-printed models and found that sutural complexity does not relate to compression resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Johnson et al 46 investigated shell strength by performing physical compression experiments on 3D-printed models and found that sutural complexity does not relate to compression resistance. Furthermore, others have found that fluted septa may actually decrease certain types of stress resistance , 44 , 47 . Concerning hydrostatic pressure, fossil occurrences and lithological data do not support a relationship between increased septal complexity and deeper habitats 48 50 .…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that vertebrate suture morphology responds to stresses imposed by behaviour and ecology ( Jaslow and Biewener, 1995 ; Clack, 2002 ; Goswami et al, 2013 ; Buezas et al, 2017 ). It has similarly long been postulated that ammonoid shell suture morphology may also respond to ecological stresses such as hydrostatic pressure ( Hewitt and Westermann, 2007 ), although there is controversy within the literature and this idea is still debated ( Lemanis, 2020 ). Remarkably, these non-homologous sutures may have convergently evolved to respond to similar external pressures.…”
Section: An Introduction To Suturesmentioning
confidence: 99%